Review of E. Taylor Atkins. 2001. Blue Nippon: Authenticating Jazz in Japan. Durham, N.C.: Duke University Press - Condry, Ian (Current Musicology, 2001)
“Thank God for Japan! It’s turning out to be a second Nevada” (209). These words of an American booking agent in the 1960s capture some of the paradoxes of jazz in Japan. On one hand, it is a jazz paradise-where else can one find jazz coffee shops (jazu kissa) that prohibit talking, but offer patrons the opportunity to listen to extensive record collections over state-of-the-art speakers? And the Japanese are not only fans. Some of japan’s jazz musicians have achieved success in the international jazz world, notably pianist Akiyoshi Toshiko, who in 1980 received three top awards from Down Beat magazine. But still, for many musicians and commentators in the West (and for some in Japan as well) there persists the enduring image that Japanese jazzers, both the fans and the musicians alike, are somewhat akin to the faux Venetian canals in Las Vegas. Aren’t they trying to be something they cannot be?